2024
DOI: 10.1111/jce.16302
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation of atrial fibrillation in “very severe” obese patients (BMI ≥ 40): Indications, feasibility, procedural safety and efficacy, and clinical outcome (the ICE‐Obese Extreme)

Lukas Urbanek,
Boris Schmidt,
Stefano Bordignon
et al.

Abstract: BackgroundManagement of atrial fibrillation (AF) in very severe obese patients is challenging. Cryoballoon ablation (CBA) represents an effective rhythm control strategy. However, data in this patient group were limited.MethodsHighly symptomatic AF patients with body mass index (BMI) ≥ 40 kg/m2 who had failed antiarrhythmic drug therapy and electrocardioversion and failure to achieve targeted body‐weight‐reduction underwent CBA.ResultsData of 72 very severe obese AF patients (Group A) and 129 AF patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is reasonable that the higher rates of puncture site complications and radiation doses were observed in obese patients, 1 given their anatomical features. However, the detailed association between obesity and the difficulty of CBA, as indicated by the longer mean time to sustained pulmonary vein isolation, remains uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable that the higher rates of puncture site complications and radiation doses were observed in obese patients, 1 given their anatomical features. However, the detailed association between obesity and the difficulty of CBA, as indicated by the longer mean time to sustained pulmonary vein isolation, remains uncertain.…”
mentioning
confidence: 99%
“…The ablation of lower pulmonary veins required more procedural time than other veins in obese patients. 1 The elevation of the diaphragm due to obesity may inhibit appropriate atrial septum puncture and make CBA to lower pulmonary veins challenging.…”
mentioning
confidence: 99%
“…In our recent "ICE-Obese Extreme" study, highly symptomatic AF patients with BMI ≥ 40 kg/m 2 who had failed AADs and ECV therapy and failed to achieve target body weight reduction underwent cryoablation, and the data showed the procedural feasibility and efficacy of cryoablation in very severe obese patients, and we concluded that in such selected patient group, catheter ablation may still serve as an effective rhythm-control option although increased technical difficulty can be expected. 5 The limitations of the study were also clearly discussed, including the single center fashion instead of multicenter trial, and the high proficiency of the primary operators (>6000 ablation experience: Chen, Chun, Schmidt, and Bordignon), which may make it difficult to generate our results to low-volume centers.…”
mentioning
confidence: 99%